Design and Evaluation of a Mobile-Based Application for Patients With Type 2 Diabetes: Case Study of Shariati Hospital in Tehran, Iran - Reza Safdari; Leila Shahmoradi; Ali Garavand; Nasim Aslani; Aliasghar Valipour; Hassan Bostan (Baqiyatallah University of Medical Sciences, 2018)
Background: With regard to the particularly high prevalence, cost, and number of disabilities associated with diabetes, increasing patients' knowledge and skills for managing the disease can help minimize the risks of complications. Objective: The present study aimed to design and evaluate a mobile-based application with which patients with type 2 diabetes can increase their knowledge of and skills for managing their disease. Methods: The current developmental-applied study was conducted in 2016 in a library and used a 2-step sectional format. The research population comprised 15 physicians and endocrinologists working in medical centers associated with Tehran University of Medical Sciences and 20 physicians and patients. Based on the library study, a checklist was designed and then distributed among participants. Their responses were analyzed using SPSS software version 20. Results: The data was divided into 4 main sections: identity information (patient demographics), clinical information, education curriculum related to diabetes management, and program requirements for diabetes management, which consisted of 52 subsets. The evaluation of the system by doctors and patients showed that the system has high capabilities. Conclusion: Mobile-based programs can help diabetics control blood glucose levels, reduce diabetes complications, and promote overall health.